PRAKTIK JUAL BELI PRICE FIXING PADA KEGIATAN CAR FREE DAY (CFD) TULUNGAGUNG DI TINJAU DARI UU NO. 5 TAHUN 1999 TENTANG LARANGAN PRAKTIK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT SERTA HUKUM EKONOMI SYARIAH - Mardhani, Yusuf; Fadilah, Zulfa Zahratul (Ahkam: Jurnal Hukum Islam, 2023)
This research is motivated by the existence of CFD activities as a government effort in maintaining environmental quality and developing MSMEs. The large number of traders at CFD activities and the large number of visitors is an opportunity to increase sales for MSMEs. Therefore, it is necessary to study in depth whether the practice of buying and selling price fixing at the Tulungagung Car Free Day (CFD) activity is in accordance with the rules when viewed from Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and Sharia Economic Law. The objectives of this study are (1) to determine the implementation of the practice of buying and selling price fixing carried out by MSMEs in the CFD Sunday Morning activity in Tulungagung reviewed from Law. No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. (2) to determine the implementation of the practice of buying and selling price fixing carried out by MSMEs in the CFD Sunday Morning activity in Tulungagung reviewed from Sharia Economic Law. This research method uses an empirical qualitative approach, namely a research method that uses field data as the main data source, such as the results of observations and interviews. The data sources in this study were primary and secondary. The analysis techniques used were data reduction and triangulation to verify data validity. The results of this study are: (1) the price-fixing practices carried out by MSMEs during Sunday morning CFD activities in Tulungagung, as viewed from Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, are in accordance with the regulations because no business actor dominates the market, has substitute goods, and market pricing is based on agreed-upon prices. (2) the price-fixing practices carried out by MSMEs during Sunday morning CFD activities in Tulungagung, as viewed from Sharia Economic Law, indicate that Jumbo Ice Tea vendors have set prices with fairness and transparency because there is no monopoly element to dominate the market, thus complying with the principles of Sharia economic law.